Hifikepunye Pohamba's rhetorical presidency: inauguration and independence anniversary speeches - Nanyeni, Frieda Nauyele (Department of Private Law, 2019)
This study examines the first inauguration speech and the four Independence anniversary speeches delivered by the former second president of Namibia, Hifikepunye Pohamba. The five volumes of these speeches, which marked Pohamba’s first term of office, plus audio-recordings of the highlights of the speeches on the Namibian Broadcasting Corporation, were the primary data of the study. Pohamba’s modern presidency, executed the laws through speeches, communicated directly to the Namibian people about what his Government have done, what it is attempting to do, and what they plan to do. In order to investigate how Hifikepunye Pohamba’s rhetoric continued in shaping democracy in the post-apartheid Namibia, the argument of the analysis was based on the Aristotelian (2007) ‘three regimes’ of rhetoric as well as the three rhetorical proofs. On the historical background information, a context of the rhetorical situation was drawn from Bitzer (1968), and the rhetorical argument and application of Perelman (1984). Moreover, close contextual analysis was also employed as it seeks to analyse the relationship between the inner working of public discourse and its historical context in order to discover what makes a particular text function persuasively. Pohamba’s speeches were analysed closely and rhetorically interpreted within their Namibian historical and political context. Thus, the study reveals the monumental occasions in the history of Namibian politics, among others, the symbolic rhetoric of the peaceful transfer of power from the founding President Sam Nujoma to the second president, who was also democratically elected, Hifikepunye Pohamba. Pohamba’s rhetoric reflects his rhetorical performative. He demonstrated his democratic ethics to his audience in his rhetoric, and constantly referred to certain individuals who were respected by his audience. Thus, he continued shaping democracy in Namibia. Pohamba’s rhetoric contains values of praising and blaming; he established fact and judgement about the past, and also advised about the future. He emphasised on the policy of national reconciliation and confirmed that reconciliation had ushered in a new dispensation of political stability, peace, unity, ethnic cohesion and security in Namibia. Namibian people must therefore continue to shun the vices of tribalism, sexism and corruption, among other things. Pohamba effectively used his rhetoric to communicate to the audience which is an important aspect of a democratic regime. This was observed internationally, which enabled Pohamba to put Namibia on the world map as he won MO Ibrahim award for African leadership at the end of his second term. However, the current study has focused only on the rhetoric of his first term.